2014
DOI: 10.1155/2014/632051
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Traffic-Induced Bridge Vibration on Rapid Repairing High-Performance Concrete for Bridge Deck Pavement Repairs

Abstract: Based on forced vibration tests for high-performance concrete (HPC), the influence of bridge vibration induced by traveling vehicle on compressive strength and durability of HPC has been studied. It is concluded that 1 d and 2 d compressive strength of HPC decreased significantly, and the maximum reduction rate is 9.1%, while 28 d compressive strength of HPC had a slight lower with a 3% maximal drop under the action of two simple harmonic vibrations with 2 Hz, 3 mm amplitude, and 4 Hz, 3 mm amplitude. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 1 publication
1
11
0
Order By: Relevance
“…Likewise, during the construction or repair of a bridge structure, the effects of vehicle-induced vibrations on early-age bridge deck repairs could not ignored, and they have been examined in many experimental investigations. Thus far, most of the previous studies have focused on how the compressive and bond strengths of “early-age” concrete bridge deck repairs that are affected by vehicle-induced vibrations show no substantial effects [31,32]. In fact, some of the results indicated that if high quality, low slump concrete was used, both the compressive and bond strength appeared to increase slightly [33].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, during the construction or repair of a bridge structure, the effects of vehicle-induced vibrations on early-age bridge deck repairs could not ignored, and they have been examined in many experimental investigations. Thus far, most of the previous studies have focused on how the compressive and bond strengths of “early-age” concrete bridge deck repairs that are affected by vehicle-induced vibrations show no substantial effects [31,32]. In fact, some of the results indicated that if high quality, low slump concrete was used, both the compressive and bond strength appeared to increase slightly [33].…”
Section: Introductionmentioning
confidence: 99%
“…The energies, those are present in bridge's environment and can be taken into the account for energy harvesting, are vibration (vehicle-induced vibrations), acoustic (vehicle noise), wind (naturally blowing wind and air surges produced due to vehicle motion), and solar. However, bridge's vibration [15][16][17] and ambient wind [18] are more reliable to be utilized for the harvesting energy on bridges.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are many pieces of research that have been carried out on asphalt pavement structure of cement concrete bridge deck which provided meaningful guidance on this research. Wang, et al [16] have studied the interface shear characteristics between the asphalt pavement structure and the concrete bridge deck pavement and found that the shear strength of SBS modified asphalt pavement over concrete bridge deck is slightly greater than that of crumb rubber modified asphalt pavement. Li, et al [17] studied the interlaminar failure modes and mechanisms of rubber powder modified asphalt, SBS modified asphalt and epoxy resin adhesive as waterproof bonding materials and found that the shear strength is greatly affected by the thickness of the waterproof adhesive layer.…”
Section: Introductionmentioning
confidence: 99%